PENERAPAN MODEL PBL (PROBLEM BASED LEARNING) SEBAGAI UPAYA MENINGKATKAN HASIL BELAJAR PESERTA DIDIK KERAGAMAN SUKU BANGSA DAN AGAMA DI NEGERIKU DI KELAS IV SD NEGERI 200107/10 - Piliang, Epa Kardila; Siregar, Rosnida; Nurbaiti, Nurbaiti; Anggraini, Nia Devi (Jurnal Ilmiah Pendidikan Dasar (JIPDAS), 2024)
This research aims to determine the use of the Problem Based Learning learning model in learning ethnic and religious diversity in my country and determine the increase in student learning outcomes in learning ethnic and religious diversity in my country after learning using the problem based learning learning model in Class IV State Elementary School 200107/ 10. In this research, the PTK (Classroom Action Research) type of research was used. Data collection techniques used were observation and tests. The subjects of this classroom action research were Class IV students at SD Negeri 200107/10 Padangsidimpuan, totaling 20 students. The object of this research is improving student learning outcomes in learning about ethnic and religious diversity in my country, class IV at SD Negeri 200107/10 Padangsidimpuan through the problem based learning model. The results of the research showed that there was an increase in the results of learning observations where the results of observations from learning activities in cycle I obtained an average score of 65, which was in the poor category. Meanwhile, in cycle II, a score of 81.25 was obtained, which was in the good category. This means that learning carried out using the PJBL learning model can be improved from cycle I learning. And there is an increase in learning outcomes which can be seen from the results of the cycle I test. It is known that out of 20 students there were 12 students who completed with a completion percentage of around 60% of the KKM score and as many as 8 students did not complete with a percentage of around 40%. The average value of the first cycle test results obtained was an average value of 71.30 in the sufficient category. Meanwhile, in the second cycle, 18 students completed with a completion percentage of around 83.8% and 2 students did not complete with a percentage of around 16.2%.